1962
DOI: 10.1029/jz067i012p04617
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of occurrence probability of spreadFat high latitudes

Abstract: At extremely high latitudes (>60°), ionospheric conditions are very complicated, and there are sometimes irregularities of electron density due to which spread F is considered to occur in the F regions, although its presence cannot always be detected on ionograms. Paying special attention to the occurrence of these conditions, we have considered three possible definitions of the occurrence probability of spread F. On the basis of each of these definitions, the latitudinal, diurnal, seasonal, and solar‐cycle va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

1963
1963
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 11 publications
3
26
0
1
Order By: Relevance
“…14 indicates a tendency of the anti-correlation with the F10.7 data; i.e., the occurrence probability decreases blobs is limited only in the period of the very low F10.7 intensity. These phenomena are similar to the results of SHIMAZAKI (1959) and SINGLETON (1968), which indicate that spread F observed by the bottomside sounder occurs more frequently during the sunspot minimum year than during the sunspot maximum year in the low latitude region. In our analyses, it has been indicated that the plasma bubbles mainly appear in the periods of the increased F10.7 value while the plasma blobs do not appear in these periods.…”
Section: Effects Of Solar Radiationssupporting
confidence: 79%
“…14 indicates a tendency of the anti-correlation with the F10.7 data; i.e., the occurrence probability decreases blobs is limited only in the period of the very low F10.7 intensity. These phenomena are similar to the results of SHIMAZAKI (1959) and SINGLETON (1968), which indicate that spread F observed by the bottomside sounder occurs more frequently during the sunspot minimum year than during the sunspot maximum year in the low latitude region. In our analyses, it has been indicated that the plasma bubbles mainly appear in the periods of the increased F10.7 value while the plasma blobs do not appear in these periods.…”
Section: Effects Of Solar Radiationssupporting
confidence: 79%
“…Our results is supported by Shimazaki [27], who demonstrated that in mid-latitude, the spread-F occurred more frequently in summer than in winter over stations in the Far East. Seasonal variations of midlatitude spread F occurrence might be related to the changes of UA-NPD [28] (upper atmosphere neutral-particle density).…”
Section: Diurnal Seasonal and Solar Activity Variation Of Spread F Osupporting
confidence: 91%
“…Ground-based measurements of spread-F and ionospheric scintillations at equatorial latitudes reveal the existence of an intense belt of ionospheric irregularities in the nighttime F region which poses serious problems for the design of communication links operating in VHF to GHz bands [ Shimazaki, 1959;Aarons et al, 1971;Craft and Westerlund, 1972]. In an effort to probe the causative mechanisms of formation of these equatorial irregularities a variety of ground-based and in-situ techniques have been employed [Farley et al, 1970;McClure and Woodman, 1972;Mozer, 1972, 1975;Balsley et al, 1972;].…”
Section: Introductionmentioning
confidence: 99%